PopularMMOs Presents : A Hole New World - Book 1 - Pat + Jen (YouTube personality); Jones, Dani, 1983- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
An accidental trip into the underworld sends Pat and Jen on an adventure, but their attempts to flee puts them face -to-face with the most evil villain of all, Evil Jen.
Keywords: Video games; Juvenile fiction; Comic books, strips, etc; Adventure stories; Comic books, strips, etc; Zombies; Juvenile fiction; Comic books, strips, etc; Unicorns -- Juvenile fiction; Comic books, strips, etc; Fantasy -- Juvenile fiction; Comic books, strips, etc; Video games; Comic books, strips, etc; Juvenile fiction; Video games; Fiction; Adventure and adventurers -- Fiction; Zombies; Fiction; Unicorns; Fiction; Fantasy; Graphic novels; Fantasy comics; Comics (Graphic works); Fantasy fiction; Action and adventure fiction; Action and adventure comics; Fiction; Comics (Graphic works); Fantasy comics; Graphic novels; Action and adventure fiction; Action and adventure comics; Fantasy fiction